The impact of zinc levels on taste change and hair loss following bariatric surgery and reporting of dietary compliance to weight loss interventions - Mozaffar, Boshra (2024)
Currently, there is significant interest in the effective treatment of obesity, particularly the implementation of a very low-calorie diet (VLCD) and the use of bariatric surgery (BS) which is a well-established long-term treatment. However, much of the contemporary research has noted that patients who have undergone bariatric surgery have reported unexplained side effects, such as a change in their sense of taste which may impact dietary compliance post-surgery. Additionally, there is limited research concerning long-term compliance with a very low-calorie diet which is a crucial aspect of pre-and post-bariatric surgery eating requirement. This thesis is divided into two sections: the first section investigates the links between taste change and zinc following BS, and the second section examines patients’ compliance with a VLCD. The over-arching theme of the thesis focuses on the speculative association of taste and hair loss following bariatric surgery with decreased circulating zinc levels, which might affect compliance to post-surgery eating requirements and the reporting of compliance to significant calorie restriction. In the initial part of the first section, a systematic review was conducted to collect evidence regarding the role of zinc in the development of taste disorders among patients who had undergone bariatric surgery and those who had not. This study used PRISMA guidelines to conduct systematic reviews of several electronic bibliographical databases, including EMBASE, PubMed, AMED, and MEDLINE, for studies concerning the effects of BS on taste, the effects of BS on zinc levels, and the effect of zinc replacement on taste. The results from this systematic review demonstrated that, according to the findings of qualitative research (conducted via questionnaires), taste change was observed in the majority of patients within a year following bariatric surgery. However, experimental investigations did not yield statistically significant evidence of taste alteration. A total of twelve investigations were conducted to examine the occurrence of zinc deficiency following bariatric surgery (BS), which revealed a notable reduction in zinc levels that persisted for six months post-surgery. The administration of zinc sulphate was found to be efficacious in enhancing taste perception in patients, apart from those with a cancer diagnosis who did not exhibit any improvement in taste following the dispensation of zinc supplements.